Indonesian Local Plant Proteases as Rennet Alternatives: Sources, Mechanisms, Coagulation Performance, and Technological Challenges - Saleha, Rischa; Apriliyani, Mulia Winirsya; Azkarahman, Aldyon Restu; Dafista, Dela; Wiryawan, Dimas; Mamduh, Muhamad Fadly Ilal; Kuncoro, Kristian Hadi; Ghiffari, Imam; Siagian, Maruahal Hari Gautama; Aprini, Gita (Jurnal Ilmu dan Teknologi Hasil Ternak, 2026)
Enzymatic coagulation determines curd formation and strongly influences cheese quality. Animal rennet remains the reference coagulant because chymosin hydrolyzes ?-casein with high substrate selectivity. Dependence on imported rennet, halal traceability requirements, production costs, and product diversification has increased interest in plant-derived coagulants from domestic resources. This descriptive review evaluates papaya, ginger, pineapple, moringa, biduri, jackfruit, and several Ficus species available or cultivable in Indonesia. The review examines plant organs, protease classes, milk-clotting activity, proteolytic activity, casein selectivity, optimum conditions, curd properties, cheese quality, safety, and application readiness. Papaya latex provides the strongest evidence for practical use through dangke production, although papain requires activity-based dosing and strict control of contact time. Ginger zingibain shows potential for coagulation at relatively high temperatures. Pineapple bromelain supports fresh cheese production and agro-industrial by-product valorization. Moringa proteases show promising ?-casein selectivity, but product-scale validation remains limited. Biduri proteases have been applied in local soft cheese, while jackfruit and Ficus latex remain less selective than conventional rennet. Plant-derived coagulants therefore require application-specific optimization, partial purification, residual activity control, and quality standards based on milk-clotting-to-proteolytic activity ratios. Successful adoption depends on matching each protease with appropriate cheese types and validating performance, safety, consistency, and scalability in Indonesia.